Telmisartan prevents high-fat diet-induced neurovascular impairments and reduces anxiety-like behavior. Issue 9 (September 2021) - Huber, Gianna; Ogrodnik, Mikolaj; Wenzel, Jan; Stölting, Ines; Huber, Lukas; Will, Olga; Peschke, Eva; Matschl, Urte; Hövener, Jan-Bernd; Schwaninger, Markus; Jurk, Diana; Raasch, Walter
Angiotensin II receptor blockers (telmisartan) prevent rodents from diet-induced obesity and improve their metabolic status. Hyperglycemia and obesity are associated with reduced cerebral blood flow and neurovascular uncoupling which may lead to behavioral deficits. We wanted to know whether a treatment with telmisartan prevents these changes in obesity. We put young mice on high-fat diet and simultaneously treated them with telmisartan. At the end of treatment, we performed laser speckle imaging and magnetic resonance imaging to assess the effect on neurovascular coupling and cerebral blood flow. Different behavioral tests were used to investigate cognitive function. Mice developed diet-induced obesity and after 16, not 8 weeks of high-fat diet, however, the response to whisker pad stimulation was about 30% lower in obese compared to lean mice. Simultaneous telmisartan treatment increased the response again by 10% compared to obese mice. Moreover, telmisartan treatment normalized high-fat diet-induced reduction of cerebral blood flow and prevented a diet-induced anxiety-like behavior. In addition to that, telmisartan affects cellular senescence and string vessel formation in obesity. We conclude, that telmisartan protects against neurovascular unit impairments in a diet-induced obesity setting and may play a role in preventing obesity related cognitive deficits in Alzheimer's disease.